Implementation of the north central Timor regent instruction number: DPMD 413.4/208/vi/2019 as a stunting management effort in the border area of the Republic of Indonesia - democratic Republic of Timor Leste (RI-RDTL) - Pala, Aplonia; Atanus, Fidelis; Binsasi, Sulistio D (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to determine the implementation of the North Central Timor Regent's instructions Number: DPMD 413.4/208/VI/2019 to tackle stunting in the border areas of the Republic of Indonesia. This research method uses qualitative methods and activities in data analysis, namely reduction, presentation, and drawing conclusions. The study results showed that the regent's instructions were quite effective in reducing the stunting rate, where there was a significant decrease. In contrast, in February 2021, the prevalence rate gradually decreased to 26.1%. However, the stunting rate in Insana Utara and Bikomi Districts, Nilulat District, which are border districts, has a prevalence rate of below 20% from 31%. The problem is that the implementation mechanism still collides with the public's apathetic attitude and the condition of the Covid 19 decision of 31%.